Public-Private Partnerships In Transport - Estache, Antonio 1957- (The World Bank, 2008)
This paper summarizes the evidence on the evolution of transport PPPs over the last 15 years or so. In the process, it provides a primer on the associated policy issues, including of the central role of project finance in the implementation of PPP policies and the debates on risk allocation in the design of PPPs. The paper also offers a discussion of the increasingly well recognized residual roles for the public sector in transport, with an emphasis on the regulatory debates surrounding the adoption of PPPs